Does scale or method matter for conservation? Application of directional and omnidirectional connectivity models in spatial prioritizations - Dertien, Jeremy S.; Baldwin, Robert F. (Frontiers in Conservation Science, 2023)
The maintenance of habitat connections between fragmented habitat patches is vital for the conservation of wildlife populations and ecosystem functioning. The awareness of connectivity issues for species conservation has resulted in a growth of connectivity modelling and the application of these results in conservation planning. Such connectivity modelling efforts can include several decisions or data limitations which could influence the connectivity results and ultimately a systematic conservation plan (SCP). However, there has been little investigation of how these different decisions on species, scale, and extent influence the ultimate conservation planning outcomes. We modeled the connectivity of northern bobwhite (Colinus virginianus), North American river otter (Lontra canadensis) and black bear (Ursus americanus) three species with varying ecological requirements, through the Congaree Biosphere Region, South Carolina, USA. We modeled habitat suitability for each species using boosted regression trees and converted these results into resistance layers for the connectivity analyses. We compared models for each species at multistate regional and local extents using directional and omnidirectional circuit theory approaches. We then used the results from each modelling combination as conservation goals for three different SCPs to determine how connectivity modelling decisions may influence geographic conservation decisions. There was substantial positive spatial correlation between the three connectivity models of each species and there appeared to be general agreement among mammals as to most important primary corridors. Across all species the greatest agreement was between the omnidirectional and local directional models as compared with the regional directional plan which highlighted a unique corridor. The omnidirectional conservation plan required the least amount of planning units to achieve its conservation goals, followed by the local and then regional directional plans that required over 200 km2 more land area to be conserved. Our results indicate that overall variations in connectivity modelling decisions may have only a moderate impact on the identification of important movement corridors for conservation at the local scale. Practitioners should base modelling decisions on the ecology of the study region, conservation question, and available computing resource.